The Relationship Between Agility And Limb Power On Lay up Accuracy Of Basketball Extracurricular At Smk N 2 Pacitan - Wulandari, Riska Ayu; Endarto Putro, Danang; Kurniasih Astuti, Ridha (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This research investigates the relationship between agility and leg power with the accuracy of basketball layups among extracurricular participants at SMK Negeri 2 Pacitan. The study, which involved 25 participants, employed a correlational approach, utilizing tests such as the dogging run for agility, the vertical jump for leg power, and a layup test for accuracy. Data were analyzed using multiple correlation techniques with IBM SPSS 21. The findings revealed significant correlations: (1) Agility and layup accuracy with r = 0.451 > r table = 0.396, contributing 20.3%; (2) Leg power and layup accuracy with r = 0.496 > r table = 0.396, contributing 24.3%; (3) Combined agility and leg power with layup accuracy, showing a significant correlation (Rx1x2y = 0.651 > r table = 0.396) and a contribution of 65.1%.